ANALISIS BIBLIOMETRIK: TREN RISET EPISTEMOLOGICAL OBSTACLE DARI TAHUN 2000 – 2022 - Ikbal Pauji; Rahmat Kusharyadi; Ahmad Zulfa Khotimi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Mathematics is an abstract science so that in the learning process it is often difficult for students to understand the material because students have learning difficulties. Learning barriers consist of 3 namely ontogenic obstacles, epistemological obstacles and didactical obstacles. In this study the aims were to find out and analyze the trend of writing an article using the epistemological obstacle theme in mathematics learning from 2000 to 2022, articles, countries of origin, authors and institutions that produced articles with the most citations and link strength using the bibliometric analysis method. The sample used is 61 search results articles using database dimensions according to the keywords that have been determined. The data is stored in csv form to be used in the VOSviewer software to obtain mapping in searching for publication trends.